ANALYSIS OF FINANCIAL DISTRESS IN COMPANIES THREATEN TO DELISTING ON THE INDONESIA STOCK EXCHANGE USING THE ALTMAN Z-SCORE MODEL - Nurul Azizah; Anwar Ramli; Anwar (Journal Management & Economics Review (JUMPER), 2023)
This study aims to determine the potential for bankruptcy experienced by companies that are threatened with delisting on the Indonesia Stock Exchange using the Altman Altman Z-Score Model. This type of research uses descriptive quantitative. The research method uses descriptive quantitative. The sample used is a company that is threatened with delisting on the Indonesia Stock Exchange. The data used is secondary data, namely the company's financial statements listed on the Indonesia Stock Exchange. The sampling technique used a purposive sample and obtained a total sample of 5 (five) companies. Data analysis techniques using the Second Altman Z-Score. The results of the study show that in the last five years the potential for bankruptcy for companies that are threatened with delisting is relatively high because the five companies have the potential to experience bankruptcy, namely PT. Bakrie Telecom Tbk. PT. Dua Putra Utama Makmur Tbk. PT. Food Sejahtera Tbk. PT. Leyand International. PT. Trikomsel Oke Tbk. The company is in the precautionary zone to the distress zone.